English Learnability of Slum Children in Dhaka, Bangladesh - Sultana, N.; Fatima, N.C. (University of Jaffna, 2025)
English Language Teaching (ELT) in the post-colonial era has gone through a process of decolonization. Kumaravadivelu (2003) defines decolonization as a complex process of taking control of the principles and practices involved in planning, learning and teaching English-a task which is yet to be accomplished (p.540). Language learnability assigns substantial significance to an individual learner’s aptitude, environmental factors, attitudes, and motivation towards learning a language. Since decolonization in ELT aims to create a more inclusive, equitable, and culturally responsive approach to teaching English, this study establishes the state of English language learnability among the slum children of Dhaka, Bangladesh, taking into account their socio-economic and educational circumstances, while also identifying the underlying factors contributing to the prevailing situation. Slum dwellers are considered, “an integral part of urban society and contribute significantly to its economy both through their labour market contribution and informal production activities”. The study is therefore based on Maslow’s hierarchy of needs theory as for children living in slums, learning a foreign language is secondary to other needs to sustain. Maslow signifies that lower level of needs must be met before an individual moves to satisfy higher level of needs. Children living in slums struggle to meet their basic needs making education a dream difficult to accomplish. Therefore, it is important to identify how much they value language learning and how it could be more attainable. A mixed method approach was used to complete the study. Seventy samples, consisting of students and their parents and teachers from schools for slum children near Dhaka, were selected using the convenience sampling technique. Data were collected through survey questionnaires, interviews, and classroom observations. Descriptive analysis was done for quantitative data and for qualitative data thematic analysis was done to identify, analyze, and interpret patterns of meaning or themes. The findings reveal socio-economic challenges faced by parents in supporting their children’s education, resulting in their children working alongside school. Limited resources for English language teaching and learning and high dropout rates are found to be responsible for the current poor state of English learnability of slum children.Their inhibition and lack of interest affect their motivation, leading to low English proficiency. Further, the English teaching method lacks emphasis on communicative language learning. The study concludes by recommending increased parental involvement, improved teaching resources, specialised English language teachers and practice of communication-based English teaching. Urgent interventions and support from the policymakers are also recommended to address the socio economic conditions faced by the slum children and to ensure inclusivity, equitability, and culturally responsive approach to teaching English to enhance the learning environment and prospects of English learnability of slum children in Bangladesh.
Keywords: Learnability; Slum children; Decolonization